Acute leukemia during pregnancy: an investigative survey of the past 11 years. (21st May 2014) - Nakajima, Y.; Hattori, Y.; Ito, S.; Ohshima, R.; Kuwabara, H.; Machida, S.; Shirasugi, Y.; Miyazaki, K.; Sakai, R.; Tomita, N.; Ando, K.; Higashihara, M.; et al.
Summary Introduction The management of pregnant women with acute leukemia is usually challenging. We collected data concerning pregnant women with acute leukemia in the Kanagawa area in Japan. Methods A questionnaire was sent to 24 institutions in the Kanagawa area. Results Data were obtained for 11 patients, median age of 31 years (range, 20–36). Eight patients had acute myeloid leukemia and three had acute lymphoblastic leukemia. Six patients were diagnosed in the first trimester of pregnancy, one in the second trimester, and four in the third trimester. Five of six patients diagnosed in the first trimester had abortions before chemotherapy, and one had an elective abortion after receiving chemotherapy. All patients diagnosed in the second or third trimester delivered live infants. Of the six patients diagnosed in the first trimester, two died of recurrent leukemia, and four remained in remission. Of the five patients diagnosed in the second or third trimester, four achieved complete remission and remained in remission. One patient died of sepsis 4 days after cesarean section. Conclusions Careful surveillance and monitoring of the fetus and close co‐operation among hematologists, gynecologists, and pediatricians are essential to successfully treat pregnant women with acute leukemia.